Indonesian Judicial Commission in Appointment Ad Hoc Judges: In Search of Constitutional Modality - Zainal Arifin Mochtar; Idul Rishan; Ayu Atika Dewi (De Jure: Jurnal Hukum dan Syari'ah, 2022)
In Indonesian Constitution, Judicial Commission had the authority to nominate the candidate Supreme Court Justice. This study aims to find the constitutional model for the authority of the Judicial Commission to propose the appointment of the Supreme Court ad hoc judges. It is doctrinal legal research using the qualitative analysis. The constitutional model was analyzed using the approach of six modalities of constitutional argument suggested by Philipp Bobbit. This study has found that, despite no explicit authority stipulated in the Indonesian Constitution, Bobbit's interpretation methods offer a constitutional perspective that from the textual, historical, doctrinal, structural, prudential, and ethical arguments, the Judicial Commission has the constitutional legitimacy of proposing the candidates for the Supreme Court ad hoc judges.